Opportunistic salpingectomy in women undergoing hysterectomy: Results from the HYSTUB randomised controlled trial. (January 2018) - Van Lieshout, L.A.M.; Pijlman, B.; Vos, M.C.; de Groot, M.J.M.; Houterman, S.; Coppus, S.F.P.J.; Harmsen, M.G.; Vandenput, I.; Piek, J.M.J.
Highlights: Opportunistic bilateral salpingectomy has no adverse effect on ovarian reserve. Surgical outcomes are not impaired by opportunistic bilateral salpingectomy. Addition of salpingectomy did not prolong surgical time or hospitalisation. Abstract: Objective: To evaluate whether opportunistic salpingectomy in premenopausal women undergoing hysterectomy for benign indications is both hormonally and surgically safe, compared with hysterectomy without salpingectomy. Study design: In this multicentre randomised controlled trial, women were randomised to undergo either hysterectomy with opportunistic bilateral salpingectomy (intervention group) or standard hysterectomy with preservation of the Fallopian tubes (control group). Main outcome measures: The primary outcome was the difference in serum anti-Müllerian hormone concentration (ΔAMH), measured pre-surgery and 6 months post-surgery. Secondary outcomes were surgical outcomes and duration of hospital stay. The sample size was powered at 50 participants per group (n = 100) to compare ΔAMH after hysterectomy with salpingectomy to ΔAMH after standard hysterectomy. Results: Between March 2013 and December 2016, 104 women, aged 30–55 years, were randomly allocated to hysterectomy with opportunistic bilateral salpingectomy (n = 52) or standard hysterectomy (n = 52). The baseline characteristics did not differ between the two groups. The median ΔAMH was −0.14 pmol/L (IQR −1.47–0.95) in the intervention group and 0.00 pmol/L (IQR −1.05–0.80) in the control group (p = 0.49). The addition of salpingectomy did not impair surgical results and it did not affect duration of hospital stay. Conclusion: Addition of opportunistic bilateral salpingectomy during hysterectomy did not result in a larger effect on ovarian reserve when compared with hysterectomy alone, neither did it affect surgical outcomes. Therefore, opportunistic salpingectomy seems to be a safe procedure in premenopausal women undergoing hysterectomy for benign gynaecological conditions.